Impact of Market Risk Premium on Share Fair Value - Alasadi, Bushra Mohamed Sami (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2024)
This research investigates how the market risk premium influences the fair value of shares traded on the Iraq Stock Exchange using the CAPM model to estimate the required rate of return. The study incorporates the risk-free rate (RF), market portfolio return (RM), and beta-processed risk premium. It addresses the knowledge gap in understanding the risk premium's impact on fair value calculation, a crucial component of the required rate of return. Employing statistical methods, including correlation coefficient measurement and simple and multiple regression analyses, the study demonstrates a significant one-to-one relationship between the risk premium and shares' intrinsic value. These findings have important implications for investors and financial analysts in accurately assessing share values based on market risk premiums.